Cytotoxic quinazoline alkaloids from the seeds of Peganum harmala. Issue 2 (15th January 2018) - Li, Sheng-Ge; Wang, Kai-Bo; Gong, Chi; Bao, Yu; Qin, Ning-Bo; Li, Da-Hong; Li, Zhan-Lin; Bai, Jiao; Hua, Hui-Ming
Graphical abstract: Abstract: Seventeen quinazoline alkaloids and derivatives, containing two pairs of new epimers, named as ( S )- and ( R )-1-(2-aminobenzyl)-3-hydroxypyrrolidin-2-one β -d -glucopyranosyl-(1 → 6)- β -d -glucopyranoside (1, 2 ), ( S )- and ( R )-vasicinone β -d -glucopyranosyl-(1 → 6)- β -d -glucopyranoside (3, 4 ), and a new enantiomer (12b ), together with six known ones (5 –8, 10, and12a ), and three pairs of known enantiomers (9, 11, and13 ), were isolated from the ethanol extracts of the seeds of Peganum harmala L.. Their structures including the absolute configuration were elucidated by using 1D and 2D NMR, and ECD calculation approaches. The cytotoxic activities of all isolated compounds were evaluated.11 showed moderate cytotoxicity against PC-3 cells with an IC50 value of 15.41 μM.